Penurunan Rasio Neutrofil terhadap Limfosit pada Pasien Tuberkulosis Sesudah Terapi Intensif - Caroline Ciptasari; Mario Steffanus; Stefanus Lembar (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2018)
Background: Tuberculosis is a health problem with a high incidence rate in Indonesia. This disease caused by bacterial infection of Mycobacterium tuberculosis, Bacterial infection will activate the body's immune response that will induce inflammatory process. Inflammation caused by bacterial infection is characterized by an increase in the number of neutrophils (neutrophilia) and a decrease in the number of lymphocytes (lymphocytopenia). Therapy is done to reduce the incidence of TB. TB therapy is divided into 2 phases, an intensive and continuous phase. This therapy was use to killing bacteria and suppressing the inflammatory response that occurs as a result of the bacterial infection. Objective: The purpose of this study was to determine the improvement of the body's immune response through the neutrophil to lymphocytes ratio (NLR) before and after intensive therapy in patients with tuberculosis. Method: The study was conducted at Atma Jaya Hospital, taking data was held from January 2017 to May 2017 with a total of 44 patients as samples. Data were collected secondary through medical record. The results were obtained using the wilcoxcon test.Result: The results of this study was NLR decrease after therapy and this result are parallel with the decrease in the number of neutrophils and the increase in the number of lymphocytes after intensive therapy. Conclusion: There is an improvement in the condition of the patient after undergoing intensive TB therapy